2021
DOI: 10.1149/2162-8777/ac2d4e
|View full text |Cite
|
Sign up to set email alerts
|

A Spin-Valve GMR Based Sensor with Magnetite@silver Core-Shell Nanoparticles as a Tag for Bovine Serum Albumin Detection

Abstract: The availability of rapid-portable instruments to monitor the bovine serum albumin (BSA) concentration is vital in the early detection of disease. In this research, an original biosensing method based on a spin-valve giant magnetoresistance as a transducer and magnetite@silver core-shell magnetic nanoparticles (MNPs) as a tag has been proposed for detecting BSA. The synthesized magnetite@silver MNPs tag size is ≈15 nm with ≈52 emu g −1 of saturation magnetization. This proposed biosensor performs rapid detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Successively, the surface of Fe 3 O 4 was modified using (3-aminopropyl)trimethoxysilane to facilitate the Ag encapsulation. The synthesizing procedure of core-shell Fe 3 O 4 @Ag has been reported in detail in the previous work [19]. The core-shell Fe 3 O 4 @Ag MNPs to be detected in this work are mostly spherical with (15 ± 2.6) nm of average size [Fig.…”
Section: Materials and Methods A Synthesis Of Fe 3 O 4 @Ag Labelmentioning
confidence: 99%
See 1 more Smart Citation
“…Successively, the surface of Fe 3 O 4 was modified using (3-aminopropyl)trimethoxysilane to facilitate the Ag encapsulation. The synthesizing procedure of core-shell Fe 3 O 4 @Ag has been reported in detail in the previous work [19]. The core-shell Fe 3 O 4 @Ag MNPs to be detected in this work are mostly spherical with (15 ± 2.6) nm of average size [Fig.…”
Section: Materials and Methods A Synthesis Of Fe 3 O 4 @Ag Labelmentioning
confidence: 99%
“…Our previous works [19], [20] have demonstrated the effective usage of the surface-functionalized MNPs, i.e., core-shell Fe 3 O 4 @Ag, as the magnetic label for GMR-based biosensors. These MNPs not only have sufficient magnetization so their concentration can be quantified using GMR sensing elements but also can bind the bovine serum albumin (BSA) spontaneously [13], [21].…”
mentioning
confidence: 99%
“…Numerous studies have been undertaken on this topic. 41,51,85,87,88 Wibowo, et al proposed the quantification method of silver-coated magnetite using a GMR chip manufactured by NVE Corp. 85 By using a similar chip, Ardiyanti, et al perform the successful quantification of GSmagnetite and streptavidin-coated MNPs. 41 Each research reveals the linear dependence of the sensor signal to the MNPs amount with the sensitivity in the order of mV/mg/mL.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Using the spin-valve GMR bulk thin film, Wibowo, et al showed the successful quantification of Fe 3 O 4 @Ag MNPs 88 as well as Fe 3 O 4 @Ag-labeled serum albumin. 87 By using an analogous GMR sensing element, Mabarroh, et al reported the detection of GS-Fe 3 O 4 as well as GS-Fe 3 O 4 labeled α-amylase enzyme. 51 The successful usage of the GMR sensor for bio-detection shows the potential usage of the TMR sensor, which has a better MR ratio than GMR thereby consuming less energy, 89 for the forthcoming BoC field.…”
Section: Experimental Observationsmentioning
confidence: 99%